Phacoemulsification of the rock‐hard dense nuclear cataract: Options and recommendations. Issue 7 (July 2018) - Foster, Gary J.L.; Allen, Quentin B.; Ayres, Brandon D.; Devgan, Uday; Hoffman, Richard S.; Khandelwal, Sumitra S.; Snyder, Michael E.; Vasavada, Abhay R.; Yeoh, Ronald
Abstract : N/A: We describe the essential steps in the successful phacoemulsification of the rock‐hard, dense cataract. Appropriate and directed preoperative history, physical examination, and diagnostics allow the surgeon to select the best incision, anesthesia, and intended surgical technique for a given dense nuclear challenge. Hard nucleus‐specific approaches for hydrodissection, pupil management, and zonular protection then allow the surgeon to approach the rock‐hard nucleus with maximum safety. Dense nuclear dismantling options are then discussed in detail along with fluidic and power modulation considerations. Various specific phacoemusification machine settings for rock‐hard cataracts from the authors representing several different phaco systems are then presented. The combination of these steps and considerations allow a more successful dense cataract removal and potential restoration of vision for patients. This paper represents the collective experience and advice of the Challenging and Complex Cataract Surgery Subcommittee.